Extraction of gallic acid from chromolaena sp. using ultrasound-assisted extraction - Afnan Azzahra, Ahmad Kamal; Suhaimi, Mohamad; Mardawani, Mohamad; Rizki, Wannahari; Ahmad Ziad, Sulaiman; Azilah, Ajit; Lim, Jun-Wei; Nurul Akmar, Che Zaudin (Chulalongkorn University, Faculty of Fine and Applied Arts, 2021)
Chromolaena sp. is believed to have phytochemical components namely alkaloids, flavonoids, flavone, essential oils, phenolics, saponins, tannins and terpenoids. In this study, ultrasound-assisted extraction (UAE) procedure was performed to extract the gallic acid from Chromolaena sp. UAE is known to be an environmentally green extraction method. This study was carried out with two different parameters which are sonication time and duty cycle. Phytochemical screening result showed the presence of phenolic compound when the dark-green colour of solution was observed. The best operating parameters to maximise the yield were as follows: sonication time of 80 minutes with yield of 3.006 mg/mL and duty cycle of 90% with yield of 3.764 mg/mL. The FT-IR result shows that presence of O-H and alkene group in the extraction samples. From the results, it can be concluded that UAE is an effective method to extract gallic acid from Chromolaena sp. The implication in this study was reducing the extraction time for the production of herbs medicine from natural resource.